Microbreweries as Attractive Tourist Destinations in the Czech Republic. - Josef VACL (Kvasný průmysl, 2014)
Beer is historically the most popular beverage on the territory of the current Czech Republic and has over a thousand years of production tradition. It was a major export commodity in the past, and it still maintains this status today as it spreads the country's fame in the world. Foreign tourists consider beer to be the country's second biggest attraction, after the historic sites. The emergence of microbreweries has become the phenomenon of the last five years. We believe that microbreweries represent an attractive but so far little exploited potential for tourism development. In many cases they become a point of interest for tourists that enriches the offering of attractions and services in small municipalities as well as in large cities. We prepared two parts of an extensive research project. In the first part we investigated in over 100 microbreweries what they offer to those involved in tourism and how they work together with travel agencies, transport companies as well as with municipalities. We investigated how they contribute to the fame of municipalities and what they do to increase the inflow of domestic and foreign tourists. In the second part of the research we investigated what role is played in the tourism development strategy in municipalities and cities by microbreweries and their products, including excursions, as well as how municipalities intend to use microbreweries in their future plans. The research conclusions verify the extent to which the assumptions of the attractiveness of beer and microbreweries for the regional development of tourism are successful.Beer is historically the most popular beverage on the territory of the current Czech Republic and has over a thousand years of production tradition. It was a major export commodity in the past, and it still maintains this status today as it spreads the country's fame in the world. Foreign tourists consider beer to be the country's second biggest attraction, after the historic sites. The emergence of microbreweries has become the phenomenon of the last five years. We believe that microbreweries represent an attractive but so far little exploited potential for tourism development. In many cases they become a point of interest for tourists that enriches the offering of attractions and services in small municipalities as well as in large cities. We prepared two parts of an extensive research project. In the first part we investigated in over 100 microbreweries what they offer to those involved in tourism and how they work together with travel agencies, transport companies as well as with municipalities. We investigated how they contribute to the fame of municipalities and what they do to increase the inflow of domestic and foreign tourists. In the second part of the research we investigated what role is played in the tourism development strategy in municipalities and cities by microbreweries and their products, including excursions, as well as how municipalities intend to use microbreweries in their future plans. The research conclusions verify the extent to which the assumptions of the attractiveness of beer and microbreweries for the regional development of tourism are successful.